The Impact of Renewable Energy, Environmental Dependence, and Socioeconomic Factors on Sustainable Regional Economic Development in Indonesia - Hamrullah, Hamrullah; Fattah, Sanusi; Saudi, Nur Dwiana Sari; Jam’an , Fitriwati (International Journal of Energy Economics and Policy, 2025)
This study examines how natural resource dependence, the shift to renewable energy, and sustainable development are connected, with a focus on what this means for Indonesia’s policies. Using data from 137 countries between 1990 and 2022, the research examines the long- and short-term effects of natural resource rents, socioeconomic factors, and human capital on renewable energy use and the Sustainable Development Index across different income groups. The study uses advanced econometric methods, including the CIPS unit root test, the Panel ARDL model with PMG estimation, and Dumitrescu–Hurlin causality tests, to address cross-sectional dependence and identify reliable links. The results show a complex picture: while having many natural resources can slow the growth of renewable energy use, it also helps improve long-term sustainable development, highlighting the role of good institutions and policy choices. Upper-middle-income countries like Indonesia have the highest average Sustainable Development Index, indicating strong development despite moderate reliance on resources. The analysis also finds a two-way relationship between renewable energy use and sustainable development and points to human capital as a key factor in advancing renewable energy. These findings suggest that Indonesia should adopt a policy approach that uses resource revenues to invest in renewable energy and build human capital. This combined strategy would help Indonesia move toward more diverse, fair, and environmentally sustainable growth.